Effects of Mentha on blood pressure: a GRADE-assessed systematic review and meta-analysis of randomized controlled trials - Faezeh Nematolahi; Abbas Mohtashamian; Ghazal Kaveh; Nasrin Sharifi; Alireza Milajerdi (BMC Complementary Medicine and Therapies)
Abstract Background Mentha consumption may associated with blood pressure improvement in humans, but the recent evidence from randomized controlled trials (RCTs) showed inconsistent results. The present study provides a systematic review and meta-analysis of RCTs to investigate the effect of Mentha on blood pressure. Methods To cover all relevant literature, a complete search was conducted across PubMed, ISI Web of Science, and SCOPUS databases before March 2024 using PRISMA guidelines. In addition, Google Scholar, SID databases, the reference lists of the related reviews, and meta-analyses were searched for this purpose. Also, a “snowball search” was applied to include other relevant trials that may have been missed. A random-effects model was used for quantitative data synthesis, with weight mean difference (WMD) and 95% confidence intervals (CI). Standard methodologies were utilized to assess kappa statistics between the authors, GRADE evidence profiles, heterogeneity, meta-regression, sensitivity analysis, and publication bias. Results Out of 476 publications identified, seven RCTs were eligible and included in this systematic review and meta-analysis. There was perfect agreement in study selection between the reviewers (К statistic, 0.86; p < 0.001). Meta-analysis showed a 1.227 mmHg reduction in systolic blood pressure (SBP) (95% CI: -6.61,4.16, p = 0.655), 2.997 mmHg reduction in long-term SBP (95% CI: -8.00,2.00, p = 0.241), 1.830 mmHg reduction in diastolic blood pressure (DBP) (95% CI: -5.06,1.40, p = 0.268), and 2.857 mmHg reduction in long-term DBP (95% CI: -6.01, 0.30, p = 0.076) after Mentha consumption in intervention group compared to control. In sub-group analysis, a statistically and clinically significant reduction in SBP and DBP was observed in the participants with ages above 30 years and in the participants with SBP > 130 mmHg or DBP > 80 mmHg. Conclusions Our findings showed that Mentha consumption might not have a statistically significant effect on lowering SBP, DBP, long-term SBP, and long-term DBP. However, it can lead to a clinically significant reduction in both long-term SBP and long-term DBP. Besides, Mentha may have potential benefits for patients with pre-hypertension and hypertension. Nevertheless, further well-designed RCTs are needed to confirm our results. PROSPERO Registration No: CRD42023459490